Instagram Influencers and Their Effect on Destination Image: Evidence from Indonesia - Adiningtyas, Rahma (2022)
As DMOs increasingly turn to Instagram influencers for marketing, it is important to understand why they are hiring influencers rather than relying on their networks to promote their destinations. People's daily lives are now influenced by social media. Many opportunities, but also many obstacles and questions, have arisen as a result of the digital era, including how to best promote companies and products on social media such as Instagram. Several businesses are now investing in influencer marketing, despite the fact that it is a widely controversial marketing approach that has yet to be well researched. This study intends to evaluate the impacts of Instagram influencers on a holiday destination image to add to this field of research. The literature review section provides a comprehensive overview of theories surrounding social media influencers. The discussions are on eWOM, opinion leadership, and Destination Image, with the addition of an overview of Indonesian tourism, which is where the data collection was performed. A framework was developed based on the literature review, which revealed the influencer’s characteristics that might impact their ability to influence people’s image of a destination, as well as the subsequent outcomes. To test the framework hypotheses, research data was collected using an online survey of 209 participants of Instagram users in Indonesia. The results revealed that credibility and popularity are significant traits that can boost an influencer’s ability to affect people’s image of a destination. Additionally, it was also evidenced that a positive destination image will lead to an increase in WOM and intention to travel. Other significant conclusions were drawn, implying that this topic could have a variety of managerial, academic, and commercial significance. Managers can use these contributions to make informed decisions about the attributes to look for when deciding whether or not to cooperate with social media influencers.